Pengembangan Media Pembelajaran Papan Baca Menggunakan Kartu Huruf Bermuatan Kearifan Lokal Suku Sasak - Nabilah, Muna Iffat; Istiningsih, Siti; Erfan, Muhammad; Tahir, Muhammad; Mansur Hakim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research aims to develop and determine the feasibility and practicality of reading board learning media using letter cards containing the local wisdom of the Sasak tribe for class II students at SDN 20 Ampenan. The research method used is research and development (Research and Development) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The research subjects were 10 class II students at SDN 20 Ampenan. The research instruments used consisted of media and material expert validation questionnaires, as well as teacher and student response questionnaires. The research results obtained were that reading board learning media using letter cards containing local wisdom of the Sasak tribe received an eligibility percentage of 87% from media experts with appropriate criteria, and 97% from both material experts with very appropriate criteria. Then, the percentage of practicality was 94.5% of student responses with very practical criteria, and 96.6% of teacher responses with very practical criteria. So, based on the research results, it can be concluded that the reading board learning media using letter cards containing the local wisdom of the Sasak tribe is declared feasible and practical for use in the reading learning process for class II students at SDN 20 Ampenan.